A cosmopolitan invader – Choreutis sexfasciella (Lepidoptera, Choreutidae) – in Cyprus: first record, molecular characterization, and a reared parasitoid - Jakovos Demetriou; Marios Aristophanous; Evangelos Koutsoukos; Eddie John; Helen E. Roy; Angeliki F. Martinou; Jadranka Rota (Nota Lepidopterologica)
The Banyan Leaf Skeletonizer moth, Choreutis sexfasciella (Sauber, 1902) (Lepidoptera: Choreutidae), is reported from Cyprus for the first time from Ficus microcarpa L.fil. and F. benjamina L. trees in urban areas of Larnaca, Limassol, and Paphos. C. sexfasciella was originally described from the Philippines and has rapidly extended its range in the last five years into several Mediterranean countries as well as into North America. DNA barcode sequencing of several specimens from Cyprus has demonstrated that they are closely related to North American specimens. The parasitoid wasp Elasmus cf. cyprianus Ferrière, 1947 (Hymenoptera: Eulophidae) has been reared from leaves infested with larvae of C. sexfasciella. The observed socioeconomic impacts of the non-native moth and the potential use of its parasitoid as a biological control agent are discussed.